PENERAPAN METODE BERPIKIR KREATIF “HAPPY” UNTUK MENDISAIN KARYA VISUAL ART ARSITEKTUR - Happy Indira Dewi; Zulfitria Zulfitria; R. Andi Ahmad Gunadi (Universitas Muhammadiyah Jakarta, 2019)
This research is a preliminary study, from a study of Creative Learning Models for Gifted Visual Art Children. Architecture is included in the applied 3-dimensional visual art criteria. The research problem is how to apply creative thinking models by Happy that are used by architectural students in designing architectural works. The research method used is descriptive kualitative method. The aim ofthe research is to know the thinking process of architectural students in the work, which will be used as a reference to develop visual art architectural creative thinking methods at the level of children. The results of this study are the application of creative thinking models by Happy can produce works that meet creative criteria, namely flexibility, originality, elaboration, fluency and completeness.